Individualism and working from home - Jan Bietenbeck; Natalie Irmert; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2024)
This paper investigates the role of individualism in explaining cross-country differences in working from home (WFH). Using data from the Current Population Survey (CPS) of the United States and the European Social Survey (ESS), we isolate the influence of individualism by comparing immigrants from different cultural backgrounds residing in the same location. We find that a 10-point increase in country-of-origin individualism, measured on a 0-100 scale, is associated with a 3.9 percentage point (pp) higher likelihood of WFH and 1.12 more weekly WFH hours in the CPS, and a 2 pp higher likelihood of frequent WFH in the ESS. Our analysis of potential mechanisms suggests that individualism influences WFH through higher educational attainment and occupational selection.
Keywords: J20; D22; E24; L23; 330; working from home; individualism; culture; epidemiological approach